Alkalization of irrigated soils suitable for orchard growing in steppe Crimea and prospects for their use - Klimenko, O. E. (Eurasian soil science, 2016)
Data of large-scale soil surveys performed by the Ukrgiprosad Institute (Ukrainian Institute for Orchard Growing) in 1997–2013 on irrigated soils of steppe Crimea reserved for orchards on the area of about 3000 ha are discussed. It is shown that all the studied soils are subjected to alkalization with the presence of soda and with an increase in concentrations of sodium and magnesium bicarbonates up to the values toxic for fruit crops. The concentrations and occurrence frequencies of alkaline salts depend on the soil type, the presence of solonetzic features, the amount of carbonates, the particular depth in the soil profile, the subsoiling, and other factors. Within the studied area, some soils are unsuitable or partly suitable for orchard growing. To improve the soil conditions for orchard growing in the areas subjected to alkalization, alkaline salts should be neutralized to nontoxic level, and the soil alkalinity should be reduced using chemical reclamation methods.